Enhancing Earth-affecting Solar Transient Observations via Novel Spacecraft Trajectories - Pedro J. Llanos (Fundamental Research and Application of Physical Science Vol. 8, 2023)
A deep understanding of earth-affecting solar transient observations is critical to help protect spacecraft in space and infrastructures on Earth. While instrumentation is crucial to collect key data to have a better understanding of solar activity, novel spacecraft trajectories can be an important aspect of the mission design to help improve such observations. This work highlights the investigation of new orbits geometries that can provide a very attractive behavior for a spacecraft to monitor space weather coming from the Sun from different angles. A number of orbit transfer mechanisms, including sub-solar orbits, quasi-satellite orbits, and short- and long-distance connections between the triangular points L4 and L5 and the collinear point L3 of the CRTBP (circular restricted three-body problem) in the Sun-Earth system, are examined as potential substitutes to observe solar activity. To this date there has not been any mission to L3, L4 or L5, but several focus mission topics have been proposed by NASA to the Sun-Earth L4 and L5 Lagrange points, and ESA’s space weather mission, Vigil, is soon to be placed in near the Sun-Earth L5 to enhance solar activity onset detection and provide better assessments of the CMEs in the corona and heliosphere.